Association of socioeconomic status with consumption of cigarettes, illicit drugs, and alcohol. Issue 2 (3rd April 2019) - Marzban, Maryam; Hadji, Maryam; Gholipour, Mahin; Rashidian, Hamideh; Rezaianzadeh, Abbas; Hasanzadeh, Jafar; Haghdoost, Ali Akbar; Rahimi-Movaghar, Afarin; Ghiasvand, Reza; Moradi, Abdolvahab; Khavari-Daneshvar, Hossein; Weiderpass, Elisabete; et al.
ABSTRACT: Introduction and Aims: Socioeconomic Status (SES) is considered as one of the important factors associated with use of various drugs. The present study aimed to investigate the effect of SES on cigarette smoking, alcohol use, drug use, and passive exposure to opium and cigarette smoke. Design and Methods: In this study, which is part of a multicenter case-control study, the research hypothesis was checked among controls who had referred to hospitals. Data were collected through a questionnaire and laboratory tests to determine the actual consumers of opium and other illicit drugs. Then, the data were analyzed using STATA 13. Result: This study was performed on 364 individuals within the age range of 30 to 75 years. More than 55% of the participants had a history of life-time consumption of cigarettes and hookah as well as alcohol and drugs. The results revealed an inverse relationship between SES and life-time consumption of hookah and alcohol. Furthermore, individuals with higher SES were more likely to deny their drug use. Discussion and Conclusions: The results revealed little robust evidence supporting the assumption that SES level can have an important effect on illicit drug use. On the other hand, the participants' characteristics could have a prominent effect on precise evaluation of the relationship between SES and drug use. Further multicenter studies are needed with samples diversified in terms of age and ethnicity to identify these confounding relationships.